Perfil clínico-epidemiológico de pacientes HIV positivos e negativos acometidos por criptococose procedentes de Cuiabá e Várzea Grande – MT – Brasil - Azevedo, Cassius Clay Scofoni Faleiros de (2017)
Cryptococcosis is caused by two distinct yeast species, Cryptococcus neoformans and Cryptococcus gattii, which cause invasive infections with significant lethality, in immunocompromised and immunocompetent individuals. In Brazil, C. gattii cryptococcosis is endemic, occurring mainly in HIV-negative individuals. C. neoformans NIV genotypes and C. gattii VGI type are the predominant genotypes in the world. However, the genotype VGII has been related to human fungal meningitis in the N and NE regions of Brazil. Cryptococcus neoformans (predominantly serotypes A and D) affects more patients with AIDS, is cosmopolitan and accounts for high rates of lethality and mortality. The objective of this work was to search for the correlation between molecular types previously characterized from clinical isolates of HIV positive and negative patients affected by cryptococcosis from the municipalities of Cuiabá and Várzea Grande in Mato Grosso and the clinical epidemiological profile of the same. Fifty-one patients with cryptococcosis were identified in the analyzed period, with 62.7% (n = 32) males and 37.8% (n = 19) females, with a mean age of 37.9 years (95% CI = 34.2-41.7), white 41.2% (n = 21), urban residents 87.0% (n = 40) and rural area 13.0% (n = 6). Among the comorbidities reported, the most frequent were: AIDS 62.7% (n = 32), smoking 27.4% (n = 14), alcoholism 11.8% (n = 6), tuberculosis 5.9% = 3), systemic arterial hypertension 5.9% (n = 3) and viral hepatitis 3.9% (n = 2). Cryptococcus neoformans was isolated in 72.5% (n = 37) of the patients, being 97.3% (n = 36) of the molecular type NIV and 2.7% (n = 1) NIV; and C. gattii in 27.5% (n = 14) of the patients, being 100.0% (n = 14) of the molecular type VGII. Regarding the clinical forms, it was observed: neurological 74.5% (n = 38), disseminated 15.7% (n = 8), pulmonary 7.8% (n = 4), cutaneous lesion 2.0% N = 1). The main antifungal drug used in treatment was amphotericin B 92.1% (n = 35). The mean dose was 704.3 mg (95% CI = 521.2-887.5). The mean time between onset of symptoms and initiation of treatment was 29.1 days (95% CI = 17.9-40.2). The mean time between the onset of symptoms and the beginning of treatment was statistically similar for both C. neoformans and C.gattii (p = 0.51). There was a statistical difference between the mean systolic blood pressure of patients with C. neoformans cryptococcosis compared to C. gattii cryptococcosis (p = 0.04). In conclusion, the clinical characteristics associated to the molecular profiles found in the two groups of patients evaluated in this study reveals the local epidemiological profile and raises the importance of knowledge of these parameters, considering that cryptococcosis is not a compulsory notification disease in the state of Mato Grosso. The molecular type associated with the circulating Cryptococcus gattii species in the two municipalities evaluated is identical to the North and Northeast regions. The consolidation of the cryptococcosis Brazil network will provide over the next years data from each state allowing over time the knowledge of the global molecular profile in the national scenario, associated with the epidemiological clinical profile of each health service that composes it.